Dopamine Dysregulation Syndrome and Deep Brain Stimulation of the Subthalamic Nucleus in Parkinson's Disease - Beatriz De la Casa-Fages; Francisco Grandas (Neurology Research International)
Dopamine dysregulation syndrome is a complication of the dopaminergic treatment in Parkinson's disease that may be very disabling due to the negative impact that compulsive medication use may have on patients' social, psychological, and physical functioning. The relationship between subthalamic nucleus deep brain stimulation and dopamine dysregulation syndrome in patients with Parkinson's disease remains unclear. Deep brain stimulation may improve, worsen, or have no effect on preoperative dopamine dysregulation syndrome. Moreover, dopamine dysregulation syndrome may appear for the first time after deep brain stimulation of the subthalamic nucleus. The outcome of postoperative dopamine dysregulation syndrome is poor despite stimulation and medication adjustments. Here we review the phenomenology and neurobiology of this disorder, discuss possible mechanisms that may underlie the diverse outcomes of dopamine dysregulation syndrome after subthalamic nucleus deep brain stimulation, and propose management strategies.